Evaluation of the funding of the National Agency for Youth Employment Support in the Establishment and Accompanying of Small and Medium Enterprises - Case Study of the National Employment Support Agency for the State of Tebessa - - Amamra, Yassmina; Malah, Wiam (Finance and Business Economies Review, 2020)
The aim of the research is to evaluate the performance of the National Agency for Youth Employment Support through its tasks of establishing and strengthening small and medium enterprises through analyzing the various procedures and stages of the construction process which require a process to accompany the establishment based on a friendly relationship between the institution and the accompanying body. The performance of the National Employment Support Agency for the State of Tebessa was assessed through the use of case-study tools to observe and analyze the various documents available to the Agency. The research found that the National Agency for Youth Employment Support of Tabessa Province achieves local development of the state through the increase in the percentage of beneficiaries of loans and the opening of employment positions for young people.